Movimiento de Regeneración Nacional: democracia interna y tendencias oligárquicas - Bolívar Meza, Rosendo (El Colegio de México A.C., 2017)
This paper aims to analyze the internal democracy and oligarchic tendencies of the National Regeneration Movement (Morena), with regard to aspects related to its internal operation in terms of the composition of power, decision making mechanisms, and forms of selection of the party leadership and of the candidates to occupy elected positions. This will be done in two ways. Firstly, from a formal and legal perspective, by analyzing its internal operation according to what the party sets out in its founding documents. Secondly, from a perspective of political reality, analyzing the party’s political process during its process of establishment and the election of its national leadership, and the first selection of party cadres for elected positions for the 2015 electoral process.